Impact of in situ physical and chemical cleaning on PVDF membrane properties and performances - Rabuni, M.F.; Nik Sulaiman, N.M.; Aroua, Mohamed Kheireddine; Ching, Yern Chee; Hashim, Nur Awanis (2015)
Appropriate selection of cleaning agent is an important factor to achieve a better cleaning efficiency and this topic has become an ongoing discussion. This work assesses the impacts of sodium hydroxide (NaOH) and sodium hypochlorite (NaOCl) aqueous solution towards polyvinylidene fluoride (PVDF) stability at the typical concentrations used in membrane cleaning. The cleaned membranes were characterised using held emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR), pure water flux measurement, contact angle, protein retention and tensile testing. Membrane cleaned at elevated temperature and higher concentration presented a higher water flux than the virgin membrane which can be a worrying sign of alteration in membrane properties. The FIR spectra indicated that the alteration in chemical composition of the membrane causes a reduction in the degree of hydrophilicity. The mechanical properties of the membrane were compromised based on the declination of tensile strength. The findings from this work suggest that the usage of NaOCl as compared to NaOH causes a more detrimental effect towards the stability of the PVDF membrane. (C) 2014 Elsevier Ltd. All rights reserved